Synthesis and Characterization of Cellulose Nano – Crystals Derived from Groundnut Shell for Metronidazole Anti-Biotic Removal - A. M. Hammari; A. J. Abubakar; A. B. Usman; Fatima M. U.; Judith S.; Jauro B. M (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This research was aimed at investigating the removal of metronidazole (MNZ) an anti-biotic from pharmaceutical wastewater simulated in the laboratory by Cellulose Nano-crystals derived from groundnut shell (CNC-GS). The influence of different factors on the adsorption rate including initial pH, adsorbent dosage, initial MNZ concentration, temperature, and contact time was evaluated. CNCs derived from Groundnut shell was shown to have percentage yield of 33.4%. Fourier transforms infrared spectroscopy, Brunauer–Emmett–Teller technique, X-ray diffraction, and Scanning Electron Microscopy characterized the CNC-GS. The results showed that under the optimal conditions (pH=3, 60 minutes of contact time, an initial MNZ concentration=250 mg/L and a CNC-GS dose of 1.5 g/L), the maximum adsorption efficiency reached 95%. Additionally, kinetic analysis revealed that the pseudo-second-order kinetic model was the most suitable, while the adsorption isotherm closely followed the Langmuir model with R2 (0.9998). The total pore volume and a micro pore volume of CNC-GS were 0.195 cm2 /g and 0.139 cm3 /g, respectively. The total surface area of the adsorbent (CNC-GS) was found to be 380.095m2 /g. Thermodynamic studies have shown that the reaction was spontaneous (=0.0016628) and endothermic (=0.21283) in nature. In conclusion, CNC-GS proved to be a highly effective adsorbent with a strong capability to remove MNZ from the contaminated water.